USER EVALUATION ANALYSIS OF THE TICKET PURCHASING FUNCTION IN THE M.TIX APPLICATION USING THE USABILITY SCALE (SUS) METHOD - Hidayah, Nur Aeni; Yusri Salsabilla, Kaila (JURNAL PERANGKAT LUNAK, 2023)
ABSTRACT The M.TIX application has several features that can be accessed anytime and anywhere. There are still some user complaints against the currently operating M.TIX application. One of them concerns the look and feel of the UI/UX which seems old-fashioned and unattractive. The purpose of this study is to analyze user ratings of the M.TIX ticket purchasing function using the system usability scale (SUS) method and recommend user interface improvements to the original application. Data collection was carried out by distributing Likert scale questionnaires online via the Google form, where the number of research samples was 61 people. The results of this study indicate that the average SUS score for the ticket purchasing function of the M.TIX application is 68.5 which is included in the Very High, OK category and is given the title D. Based on this, UI/UX needs to be improved, and see also the performance of the application. M. TIX